THE ROLE OF MORALITY IN A LEGAL SYSTEM IN THE CONTEXT OF THE WESTERN LEGAL TRADITION - Randakevičiūtė, Jurgita (Teisė, 2017)
In this article, the role of morality in a legal system in the context of the Western legal tradition is analysed from the perspective of three legal paradigms (legal positivism, natural law and legal realism), in order to lay the foundations for a more consistent interpretation of the Art. 53 (a) EPC.